Selective Electroreduction of CO2 to n‐Propanol in Two‐Step Tandem Catalytic System. Issue 36 (11th August 2022) - Wu, Guoling; Song, Yaru; Zheng, Qiang; Long, Chang; Fan, Ting; Yang, Zhongjie; Huang, Xuewei; Li, Qun; Sun, Yali; Zuo, Lulu; Lei, Shengbin; Tang, Zhiyong
Abstract: Electrocatalytic reduction of CO2 (CO2 RR) to high‐energy‐density C3 fuels like n ‐propanol has been widely recognized as one of the core technologies for both renewable energy storage and carbon neutrality. Unfortunately, exceptional catalytic sites that are able to simultaneously implement efficient conversion to C1 and C2 products are difficult to design for single electrolyzers, leading to poor activity and selectivity toward n ‐propanol. Alternatively, electroreduction of CO (CORR) has shown good performance toward C3 fuels, but the cost and safety of gas storage hinder its industrialization. Herein, a system consisting of two tandem electrolyzers for converting CO2 to CO and CO to n ‐propanol, respectively, is constructed. Beyond the reported tandem electrodes and one‐pot tandem catalysts, precise voltage control over tandem electrolyzers enables optimizing the conversion of both CO2 RR to CO and CORR to n ‐propanol. Significantly, an unprecedented Faradaic efficiency of 15.9% for n‐propanol along with corresponding half‐cell power conversion efficiency of 19.3% is achieved. Abstract : An efficient two‐step tandem catalytic CO2 RR system targeting n ‐propanol is set up. 3D single‐atom nickel and multi‐hollow Cu2 O electrocatalysts are used in CO2 ‐to‐CO and CO‐to‐propanol conversion steps, respectively. The unique advantages of versatile choice of catalysts and easy control over the step process make the tandem catalytic strategy open a new avenue toward obtaining value‐added multi‐carbon products by CO2 RR.